Risk of Hepatocellular Carcinoma in Patients Treated With Entecavir vs Tenofovir for Chronic Hepatitis B: A Korean Nationwide Cohort Study - Choi, Jonggi (JAMA Oncol, 2018)
IMPORTANCE: Entecavir and tenofovir disoproxil fumarate have comparable efficacy in achieving surrogate end points, including virologic response, and are equally recommended as first-line treatments for patients with chronic hepatitis B (CHB). However, it is unclear whether treatment with these drugs is associated with equivalent clinical outcomes, especially development of hepatocellular carcinoma (HCC). OBJECTIVE: To compare entecavir and tenofovir in terms of the risk of HCC and death or liver transplant in patients with CHB infection. DESIGN, SETTING, AND PARTICIPANTS: A nationwide historical population cohort study involving treatment-naive adult patients with CHB who started treatment with entecavir (n = 11 464) or tenofovir disoproxil fumarate (n = 12 692) between January 1, 2012, and December 31, 2014, using data from the Korean National Health Insurance Service database. As validation, a hospital cohort of patients with CHB treated with entecavir (n = 1560) or tenofovir (n = 1141) in a tertiary referral center between January 1, 2010, and December 31, 2016, were analyzed. Nationwide cohort data were retrieved from January 1, 2010, to December 31, 2016, and hospital cohort data from January 1, 2010, to October 31, 2017. MAIN OUTCOMES AND MEASURES: Cumulative incidence rates of HCC and death and transplant rates. RESULTS: Among the population cohort of 24 156, the mean (SD) age was 48.9 (9.8) years, and 15 120 patients (62.6%) were male. Among the hospital cohort of 2701, the mean (SD) age was 48.8 (10.5) years and 1657 patients (61.3%) were male. In the population cohort, the annual incidence rate of HCC was significantly lower in the tenofovir group (0.64 per 100 person-years [PY]) than in the entecavir group (1.06 per 100 PY). By multivariable-adjusted analysis, tenofovir therapy was associated with a significantly lower risk of HCC (hazard ratio [HR], 0.61; 95% CI, 0.54-0.70) and all-cause mortality or transplant (HR, 0.77; 95% CI, 0.65-0.92) compared with entecavir. The tenofovir group also showed a significantly lower risk of HCC in the 10 923–pair propensity score–matched population cohort (HR, 0.62; 95% CI, 0.54-0.70) and 869-pair propensity score–matched hospital cohort (HR, 0.68; 95% CI, 0.46-0.99) compared with the entecavir group. CONCLUSIONS AND RELEVANCE: This study suggests that tenofovir treatment was associated with a significantly lower risk of HCC compared with entecavir treatment in a population-based cohort of adults with CHB; these findings were validated in a hospital cohort. Given the poor prognosis of patients with HCC, these findings may have considerable clinical implications in prevention of this cancer in patients with CHB infection.